2015
DOI: 10.1038/labinvest.2015.52
|View full text |Cite
|
Sign up to set email alerts
|

CDX2 homeoprotein is involved in the regulation of ST6GalNAc-I gene in intestinal metaplasia

Abstract: De novo expression of Sialyl-Tn (STn) antigen is one of the most common features of intestinal metaplasia (IM) and gastric carcinomas, and its biosynthesis has been mostly attributed to ST6GalNAc-I activity. However, the regulation of this glycosyltransferase expression is not elucidated. In IM lesions and in the intestine, CDX2 homeobox transcription factor is co-expressed with STn and ST6GalNAc-I. We therefore hypothesized that CDX2 might induce STn expression by positive regulation of ST6GalNAc-I. We showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Interestingly, when we looked more in general for proteins that were different between the high binding cell lines (HT29 and HCT116) and the low MGL-binding cell line (LS174T), we observed the cluster of mucins ( Figure S4 ) in close proximity to the transcription factor CDX-2. Together with CDX-1, this protein acts as a transcription factor that in cooperation with HNF4A and 1A, is involved in the regulation of multiple intestinal specific genes [ 26 ], as well as fucosyltransferases [ 27 ] and α2,6-sialyltransferase [ 28 ]. CDX-1 is very similar to CDX-2, and these proteins share several tryptic peptides, but we did not observe a unique CDX-1 peptide in our dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, when we looked more in general for proteins that were different between the high binding cell lines (HT29 and HCT116) and the low MGL-binding cell line (LS174T), we observed the cluster of mucins ( Figure S4 ) in close proximity to the transcription factor CDX-2. Together with CDX-1, this protein acts as a transcription factor that in cooperation with HNF4A and 1A, is involved in the regulation of multiple intestinal specific genes [ 26 ], as well as fucosyltransferases [ 27 ] and α2,6-sialyltransferase [ 28 ]. CDX-1 is very similar to CDX-2, and these proteins share several tryptic peptides, but we did not observe a unique CDX-1 peptide in our dataset.…”
Section: Resultsmentioning
confidence: 99%
“…Another group studied the gastric cancer cell line MKN45, which expresses very high levels of ST6GalNAc-I and, consequently, higher sialyl-Tn levels. In this cell line, loss of ST6GalNAc-I resulted in reduced proliferation, migration, invasion, and reduced STAT5b phosphorylation and IGF-1 expression [66,67]. Ozaki et al reported increased peritoneal metastasis of sialyl-Tn-expressing gastric carcinoma cell lines when transplanted into nude mice [68].…”
Section: St6galnac-i Dependent Mucin Glycosylation In Gastric Cancermentioning
confidence: 96%
“…ST6GalNAc-I has been also identified to be overexpressed in IM and its detection co-localizes, at the cellular level, with STn expression, being restricted to the perinuclear region [ 85 ]. The CDX2 homeobox transcriptor factor, normally expressed in intestinal cells, has been shown to regulate ST6GALNAC1 gene leading to the overexpression of STn [ 86 ].…”
Section: O- Glycosylation Alterations During Gamentioning
confidence: 99%